Does Cultural Context Affect the Association Between Self-Control and Problematic Alcohol Use Among Juveniles? A Multilevel Analysis of 25 European Countries. (February 2013) - Podaná, Zuzana; Buriánek, Jiří
The article studies self-reported alcohol consumption of European juveniles and examines its link to the level of their self-control, making use of data from International Self-Report Delinquency Study 2 (ISRD-2). The proportion of problematic drinkers and the mean level of self-control as well as the strength of the association differs among European countries. Following Gottfredson and Hirschi's general theory of crime, two hypotheses are tested, focusing on different degrees of social tolerance of juvenile drinking and alcohol availability (i.e., opportunity). Findings based on logistic multilevel models for several indicators of problematic alcohol use suggest that social tolerance (reflected in the level of cultural acceptance of juvenile drinking and in the level of policy strictness) can indeed explain the cross-national differences in the strength of self-control–problematic drinking relationship, while the contribution of opportunity is questionable in this respect. Opportunity, however, is highly relevant when explaining cross-cultural differences in the extent of problematic drinking.